Monte Carlo simulation applied in total reflection X-ray fluorescence: Preliminary results - Meira, Luiza L. C. [UNESP]; Inocente, Guilherme F. [UNESP]; Vieira, Letícia D. [UNESP]; Mesa, Joel [UNESP] (AIP Publishing, 2013)
The X-ray Fluorescence (XRF) analysis is a technique for the qualitative and quantitative determination of chemical constituents in a sample. This method is based on detection of the characteristic radiation intensities emitted by the elements of the sample, when properly excited. A variant of this technique is the Total Reflection X-ray Fluorescence (TXRF) that utilizes electromagnetic radiation as excitation source. In total reflection of X-ray, the angle of refraction of the incident beam tends to zero and the refracted beam is tangent to the sample support interface. Thus, there is a minimum angle of incidence at which no refracted beam exists and all incident radiation undergoes total reflection. In this study, we evaluated the influence of the energy variation of the beam of incident x-rays, using the MCNPX code (Monte Carlo NParticle) based on Monte Carlo method. © 2013 AIP Publishing LLC.
Keywords: Diagnostic X-ray; Monte Carlo Simulation; Synchrotron Radiation; TXRF